Amyloid myopathy: a diagnostic challenge - Heli Tuomaala; Mikko Kärppä; Hannu Tuominen; Anne M. Remes (MDPI AG, 2009)
Amyloid myopathy (AM) is a rare manifestation of primary systemic amyloidosis (AL). Like inflammatory myopathies, it presents with proximal muscle weakness and an increased creatine kinase level. We describe a case of AL with severe, rapidly progressive myopathy as the initial symptom. The clinical manifestation and muscle biopsy were suggestive of inclusion body myositis. AM was not suspected until amyloidosis was seen in the gastric mucosal biopsy. The muscle biopsy was then re-examined more specifically, and Congo red staining eventually showed vascular and interstitial amyloid accumulation, which led to a diagnosis of AM. The present case illustrates the fact that the clinical picture of AM can mimic that of inclusion body myositis.